Integrated Leafcurl Disease Control on Tobacco Plants in Klaten, Central Java - Heri Widarta; Sedyo Hartono; Sri Sulandari; Cahyo Hertanto; Erna Anastasia (Universitas Gadjah Mada, 2017)
Vorstenlanden tobacco is the best product of PT Perkebunan Nusantara X (PTPN X) Klaten, Central Java that is commonly produced into high economic value cigars. During the planting season of 2010/2011, there was an epidemy of leaf curl disease that caused billion rupiahs financial loss. Several efforts had been done, including the use of pesticides, but the result had not been satisfactory. Therefore, this research aimed to identify the pathogen of tobacco leaf curl disease and conduct integrated control system using three combinations in the nursery [A (biological agents treatment, plastic screenhouse, without physical barrier); B (biological agents treatment, plastic screenhouse + screen plot, with physical barrier of single screen, and sprayed insecticide); C (biological agents treatment, plastic screenhouse + single screen plot, with physical barrier of double screens, and fogging using white oil + insecticide)] and planting area [A (physical barrier of single screen and sprayed insecticide); B (physical barrier of single screen, sprayed insecticide, and sanitation of broad leaf weed + eradication of infected plant); C (physical barrier of double screens, fogging white oil + insecticide, and sanitation of broad leaf weed + eradication of infected plant)]. The result showed that leaf curl disease that occured at PTPN X Klaten was caused by Begomovirus, based on PCR result using Krusty and Hommer primers for Begomovirus Coat Protein gene. The most effective integrated disease control of leaf curl disease in the nursery was C combination, that consisted of biological agents treatment on the seedlings medium, screenhouse covered by plastic and double screens that was combined with physical barrier of double screens around the field, and fogging using white oil+insecticide of pyrethroid active ingredient. The most effective integrated disease control of leaf curl disease in the field was the same C combination, that consisted of the use of physical barrier of double screens, environmental sanitation of weeds around the field and eradication of infected plants and fogging using white oil + insecticide of pyretroid active agent. IntisariTembakau vorstenlanden merupakan produk andalan PT Perkebunan Nusantara X (PTPN X) Klaten, Jawa Tengah sebagai bahan baku cerutu yang bernilai ekonomi tinggi. Pada musim tanam 2010/2011 telah terjadi epidemi penyakit keriting atau kerupuk tembakau dengan kerugian mencapai milyaran rupiah. Upaya pengendalian yag telah dilakukan dengan mengandalkan pestisida tidak memberikan hasil yang memuaskan. Oleh karena itu, penelitian ini ditujukan untuk mengidentifikasi patogen penyebab penyakit kerupuk tembakau dan melakukan pengendalian secara terpadu dengan menggunakan tiga macam kombinasi yang dilakukan di pembibitan [A (perlakuan agens hayati, penyungkupan plastik, tanpa barier fisik ); B (perlakuan agens hayati, penyungkupan, barier fisik tunggal, dan penyemprotan insektisida); C (perlakuan agens hayati, penyungkupan, barier fisik ganda, dan aplikasi white oil)] dan di lahan pertanaman [A (barier fisik tunggal dan insekstisida); B (barier fisik tunggal, insektisida, dan sanitasi gulma); C (barier fisik ganda, white oil + insektisida, dan sanitasi gulma)]. Hasil penelitian menunjukkan bahwa penyakit kerupuk tembakau di PTPN X Klaten disebabkan oleh Begomovirus berdasarkan hasil PCR menggunakan primer Krusty dan Hommer untuk gen Coat Protein Begomovirus. Pengendalian terpadu penyakit kerupuk di pembibitan yang paling efektif adalah kombinasi C yang terdiri dari perlakuan agens hayati pada media bibit, penyungkupan rangkap plastik + waring ganda dipadukan dengan barier fisik berupa waring ganda sekeliling lahan dan aplikasi white oil + insektisida berbahan aktif piretroid dengan cara fogging. Demikian juga pengendalian terpadu penyakit kerupuk di lapangan yang paling efektif adalah kombinasi C yang terdiri dari perlakuan agens hayati pada media bibit, sanitasi gulma di sekitar lingkungan pertanaman dan eradikasi tanaman sakit, penyungkupan rangkap plastik + waring ganda dipadukan dengan barier fisik berupa waring ganda sekeliling lahan dan aplikasi white oil + insektisida berbahan aktif piretroid dengan cara fogging.